Fostering Self -directed Learning Within Efl Master Training Constraints- The Case Of Msila University - Bouazid , Tayeb (El Omda in Linguistics and Discourse Analysis, 2023)
The present study aims at shedding some light on self-directed learning as enhanced by adult EFL Master tertiary learners. The research consists in showing learners how independent knowledge, coupled with self-taking initiatives in the British Literature module. A mixed method was used in the study. To collect data questionnaires, interviews and observations were used. Though constrained, learners showed great talent in preparing their power points related to literary currents and movements. The study embraced 48 Civ and Lit stream students who got their assignments, did some research and collected their information to prepare their portfolios. Learners of low self-direction were backed up by the teacher. Observations have shown that the more self-directed learning grows, the better the learning control is structured by the learners who are immersed in the activities as responsible teachers doing their work. Learners tried their chances for self-directness to apply and evaluate their outcomes.